Rangkap Jabatan Menteri Sebagai Pimpinan Partau Politik Dalam Sistem Ketatanegaraan Di Indonesia - Panigfat, Ibnu Arradzie; Pietersz, Jemmy Jefry; Nirahua, Garciano (Jurnal Saniri, 2023)
According to Law Number 39 of 2008 concerning State Ministries, Article 23 to be precise states that ministers are prohibited from holding concurrent positions if the position in question is as another state official or being the head of an organization financed by the State Revenue Budget/Regional Revenue Budget. The problem that then arises is that there have been several cases of ministers holding concurrent positions as leaders of political parties. So this clearly violates the regulations regarding ministers who are prohibited from holding concurrent positions. For this reason, the implementation of the practice of holding multiple positions by ministers as leaders of political parties is not in accordance with Law Number 39 of 2008.The purpose of this study is to find out and analyze concurrent positions in accordance with the rules and regulations carried out by ministers and to find out and analyze the legal consequences of multiple ministerial positions as leaders of political parties. The research used in this writing is normative legal research.The results of this study explain that the concurrent positions carried out by the minister are in conflict with laws and regulations which have ignored Article 23 of Law Number 39 of 2008 regarding the prohibition of concurrent ministerial positions, and the legal consequences of concurrent ministerial positions as leaders of political parties will be dismissed based on President's prerogative for ministers who hold concurrent positions.